Electrical resistivity and thermopower of hole-doped delafossite CuCoO2 polycrystals. (8th January 2021) - Kurita, K.; Yagisawa, M.; Okazaki, R.
Abstract: We have synthesized the polycrystalline samples of the delafossite oxide CuCo1− y Mg y O2 through the thermal decomposition of copper–cobalt–magnesium hydroxycarbonates. As is expected from the theoretical calculations, relatively large thermopower of S ∼ 700 μ V K −1 is observed at room temperature in the parent compound CuCoO2, whereas the resistivity is too high even in the doped compounds compared with other thermoelectric oxides. The high-temperature transport is thermal-activation type characterized by two energy gaps, Δ ρ and Δ S, which are estimated from the resistivity and the thermopower, respectively. In the parent compound, we obtain Δ ρ ≃ 0.47 eV and Δ S ≃ 0.38 eV. We find that Δ ρ is larger than Δ S in all the samples, implying a mobility gap opening due to a grain-boundary scattering.